2016
DOI: 10.1080/02770903.2016.1185439
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of oral corticosteroids prescriptions in children with asthma in early childhood

Abstract: Objective: Severe asthma exacerbations are often treated with short courses of oral corticosteroids (OCS). This study assessed the incidence of OCS being prescribed in asthmatic children of various age groups and calculated their chances of receiving subsequent OCS prescriptions. Methods: Longitudinal Dutch community pharmacy data of 2272 children who were regular users of asthma medication was analyzed retrospectively. Incidence rates for first, second and third prescriptions of OCS were calculated, stratifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…In an analysis of health plan computerised claims data, 2-5% of children with asthma received three or more bursts per year, with more in the youngest (aged 1-8 years) than in the oldest children [91]. The frequent repeated prescription of OCS bursts in preschool-aged children with asthma (<4years of age) was also shown in a Dutch study [92]. In the school-aged children with severe asthma from the U-BIOPRED cohort, the median was 3 severe exacerbations requiring OCSs in the previous year [90].…”
Section: Paediatric Aspectsmentioning
confidence: 80%
“…In an analysis of health plan computerised claims data, 2-5% of children with asthma received three or more bursts per year, with more in the youngest (aged 1-8 years) than in the oldest children [91]. The frequent repeated prescription of OCS bursts in preschool-aged children with asthma (<4years of age) was also shown in a Dutch study [92]. In the school-aged children with severe asthma from the U-BIOPRED cohort, the median was 3 severe exacerbations requiring OCSs in the previous year [90].…”
Section: Paediatric Aspectsmentioning
confidence: 80%
“…In a Dutch study based on pharmacy data, more than 25% of asthmatic children were prescribed oral CS during a year of follow‐up; the risk of a second and even a third CS course during the same year was increased in infants, during their first year of life . Such finding was confirmed in an American retrospective study, reporting that children receiving the biggest amount of oral CS prescriptions were those aged 1‐4 years .…”
Section: Corticosteroids In Preschool Children With Wheezingmentioning
confidence: 82%
“…In the Netherlands, a longitudinal follow-up study of 2272 children 4 to 12 years of age who were regular users of asthma medication found that 25.7% of their sample was prescribed an OCS. 9 to 2006. 18 Our rates were similar to the 48.7% observed among infants with wheezing in the first year of life in the city of Belo Horizonte, Brazil.…”
Section: Resultsmentioning
confidence: 99%
“…8 Concerns have begun to be raised about high rates of OCS prescribing among children with asthma. 9 Texas Children's Health Plan (TCHP) is a large, not-for-profit Medicaid and Children's Health Insurance Program (CHIP) managed care organization serving the greater Harris and Jefferson county areas in East Texas, including the cities of Houston and Beaumont/Port Arthur. The specific aim of this study is to describe the rates of OCS dispensing among children with asthma who were enrolled in TCHP and to determine patient and provider factors associated with variation in OCS dispensing.…”
mentioning
confidence: 99%